2019
DOI: 10.1002/lary.27899
|View full text |Cite
|
Sign up to set email alerts
|

Tonsil size and outcome of uvulopalatopharyngoplasty with tonsillectomy in obstructive sleep apnea

Abstract: Objectives/Hypothesis To investigate the relationship of tonsil volume and grade on outcomes of uvulopalatopharyngoplasty (UPPP) with tonsillectomy in patients with obstructive sleep apnea (OSA). Study Design Retrospective cohort analysis. Methods Data of 70 consecutive patients undergoing UPPP with tonsillectomy between 2015 and 2018 were analyzed. Patients with an apnea‐hypopnea index (AHI) <10/hr or concomitant surgery other than nasal surgery were excluded. Tonsil volume was measured intraoperatively. Preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(59 reference statements)
0
14
0
1
Order By: Relevance
“…37 In patients who received UPPP, AHI reduction was significantly greater when the resected tonsil volume was greater. 38 Langin et al also confirmed the correlation between greater oropharynx space in images and improvement in the AHI following UPPP. 39 In this study, greater resected BOT volume and better improvement in AHI were strongly correlated.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…37 In patients who received UPPP, AHI reduction was significantly greater when the resected tonsil volume was greater. 38 Langin et al also confirmed the correlation between greater oropharynx space in images and improvement in the AHI following UPPP. 39 In this study, greater resected BOT volume and better improvement in AHI were strongly correlated.…”
Section: Discussionmentioning
confidence: 83%
“…Greater volume of BOT removed was predictive of surgical success 37 . In patients who received UPPP, AHI reduction was significantly greater when the resected tonsil volume was greater 38 . Langin et al also confirmed the correlation between greater oropharynx space in images and improvement in the AHI following UPPP 39 .…”
Section: Discussionmentioning
confidence: 93%
“…A PT grading scale has been used to predict OSA severity and the efficacy of tonsillectomy in treating OSA. A higher grade, which corresponds with larger and more exophytic tonsils, corresponds with higher preoperative AHI values and a more significant reduction in AHI after removal 1669,1671 . A small series noted improvement in AHI in selected patients with small tonsils after tonsillectomy 1672 .…”
Section: Surgical Treatment For Osamentioning
confidence: 97%
“…However, we provide a different surgical concept whether tonsillectomy need to be included for correction of lateral pharyngeal wall collapse. Bilateral tonsil hypertrophy might be one of the causes of lateral pharyngeal wall narrowing in subjects with OSA, and tonsillectomy may still be the most appropriate procedure among surgical options to improve lateral pharyngeal wall narrowing in a select group of subjects whose tonsil size is beyond grade 3 [ 17 , 18 , 30 ]. In these cases, lateral pharyngeal wall narrowing would not be effectively corrected if subjects with OSA did not undergo tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%